English English - Elzagi, Verliana; Buntu Laulita, Nasar (Universitas Dr. Soetomo, 2024)
This study aims to fill gaps in the literature by examining the influence of hedonic value and customer experience on repurchase decisions in foreign brand retail in Indonesia, with customer satisfaction as a mediating factor. The study utilizes a quantitative approach, collecting data via questionnaires from 202 respondents who have purchased from foreign brand retailers such as ZARA, Uniqlo, H&M, Miniso, and Sephora in Indonesia. The findings reveal that hedonic value and customer experience significantly influence customer satisfaction and repurchase decisions. However, customer satisfaction does not mediate the effects of either hedonic value or customer experience on repurchase decisions. This research introduces a novel perspective by showing that customer satisfaction may not always play a mediating role in consumer decision-making processes within the context of foreign brand retail. These results have practical implications for retail managers seeking to enhance consumer loyalty through hedonic and experiential strategies, while also contributing to academic discussions on consumer behavior.